Adenosine A1 Receptor Antagonism Abolished the Anti-seizure Effects of Exogenous Ketone Supplementation in Wistar Albino Glaxo Rijswijk Rats - Kovács, Zsolt; D’Agostino, Dominic P.; Dobolyi, Arpád; Ari, Csilla (Frontiers in Molecular Neuroscience, 2017)
The state of therapeutic ketosis can be achieved by using the ketogenic diet (KD) or exogenous ketone supplementation. It was suggested previously that the adenosinergic system may be involved in the mediating effect of KD on suppressing seizure activity in different types of epilepsies, likely by means of adenosine A1 receptors (A1Rs). Thus, we tested in the present study whether exogenous ketone supplements (ketone ester: KE, 2.5 g/kg/day; ketone salt/KS + medium chain triglyceride/MCT: KSMCT, 2.5 g/kg/day) applied sub-chronically (for 7 days) by intragastric gavage can modulate absence epileptic activity in genetically absence epileptic Wistar Albino Glaxo/Rijswijk (WAG/Rij) rats. The number of spike-wave discharges (SWDs) significantly and similarly decreased after both KE and KSMCT treatment between 3rd and 7th days of gavage. Moreover, blood beta-hydroxybutyrate (βHB) levels were significantly increased alike after KE and KSMCT gavage, compared to control levels. The SWD number and βHB levels returned to the baseline levels on the first day without ketone supplementation. To determine whether A1Rs can modify ketone supplement-evoked changes in absence epileptic activity, we applied a non-pro-epileptic dose of a specific A1R antagonist DPCPX (1,3-dipropyl-8-cyclopentylxanthine) (intraperitoneal/i.p. 0.2 mg/kg) in combination with KSMCT (2.5 g/kg/day, gavage). As expected, DPCPX abolished the KSMCT-evoked decrease in SWD number. Thus, we concluded that application of exogenous ketone supplements may decrease absence epileptic activity in WAG/Rij rats. Moreover, our results suggest that among others the adenosinergic system, likely via A1Rs, may modulate the exogenous ketone supplements-evoked anti-seizure effects.